“Ex Vivo” Influence of Fatty Acids from Plasma Cholesterol and Triglycerides on the Fatty Acid Pattern of Platelets - Aznar, Justo; Santos, Teresa; Vallés, Juana (Thrombosis and Haemostasis, 1985)
We have studied “ex vivo”, in 92 normal subjects, the influence of fatty acids (FA) that esterify plasma cholesterol and triglycerides on the fatty acid composition of phospholipids, triglycerides and free fatty acid fractions in platelets.High and significant correlations (p <0.001) were found for some of the platelet phospholipid FA and the same FA that esterify plasma cholesterol [18:11 (r = 0.56); 18:2 (r = 0.71) and 20:5 (r = 0.42)] and plasma triglycerides [18:1* (r = 0.57) and 18:2 (r = 0.66)]. Some significant correlations were also found between some of the platelet triglyceride FA and the same FA that esterify plasma phospholipids [18:1 (r = 0.58)], triglycerides [18:1 (r = 0.51), 18:2 (r = 0.52)] cholesterol [18:1 (r = 0.44)] and plasma free fatty acids [18:1 (r = 0.39); 18:2 (r = 0.40)].By evaluating these results in conjunction with those of an earlier study (1), it can be concluded that “ in vivo” the FA from different plasma lipid fractions and especially those esterifying the plasma cholesterol and phospholipid fractions, can influence the FA composition of platelet phospholipids in normal subjects. In trying to interpret the role played by plasma lipids in platelet lipids, it may be of interest to take into account the interrelationships found in this study.
Keywords: Platelets; Fatty acids; Plasma cholesterol; Plasma triglycerides; Platelet fatty acid renovation